2018
DOI: 10.1111/php.13033
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Photophysical and Photochemical Properties of Dyes in the Presence of Low Generation Amino‐terminated Polyamidoamine Dendrimers

Abstract: The photophysical and photochemical properties of the xanthene dyes mercurochrome (MCr) and eosin-Y (Eos); and the phenazine dye safranine-O (SF) are evaluated in the presence of amino-terminated polyamidoamine (PAMAM) dendrimers of low generations. The dendrimers produce a red shift in the UV-vis absorption spectra of the dyes, which increases with concentration and the size of the PAMAM molecule. The Stern-Volmer plots of fluorescence quenching for xanthenic dyes present a downward curvature. It is ascribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In previous works, we demonstrated that under visible LED light xanthene dye/PAMAM couples generate radicals with high efficiency because amino groups in the dendrimer structure act as electron donors to excited dyes. [15][16][17] In addition, we found that the strong dye/PAMAM binding is a key factor in the electron transfer process. Such features along with the water solubility of PAMAM make these dye/dendrimer combinations excellent candidates for their use in solvent-free formulations, thus reducing the environmental impact of typical PIs.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In previous works, we demonstrated that under visible LED light xanthene dye/PAMAM couples generate radicals with high efficiency because amino groups in the dendrimer structure act as electron donors to excited dyes. [15][16][17] In addition, we found that the strong dye/PAMAM binding is a key factor in the electron transfer process. Such features along with the water solubility of PAMAM make these dye/dendrimer combinations excellent candidates for their use in solvent-free formulations, thus reducing the environmental impact of typical PIs.…”
Section: Introductionmentioning
confidence: 83%
“…In previous works, we demonstrated that under visible LED light xanthene dye/PAMAM couples generate radicals with high efficiency because amino groups in the dendrimer structure act as electron donors to excited dyes [15–17] . In addition, we found that the strong dye/PAMAM binding is a key factor in the electron transfer process.…”
Section: Introductionmentioning
confidence: 84%